Response assessment after stereotactic body radiotherapy for spinal metastasis: a report from the SPIne response assessment in Neuro-Oncology (SPINO) group. Issue 16 (December 2015) - Thibault, Isabelle; Chang, Eric L; Sheehan, Jason; Ahluwalia, Manmeet S; Guckenberger, Matthias; Sohn, Moon-Jun; Ryu, Samuel; Foote, Matthew; Lo, Simon S; Muacevic, Alexander; Soltys, Scott G; Chao, Samuel; et al.
Summary: The SPine response assessment In Neuro-Oncology (SPINO) group is a committee of the Response Assessment in Neuro-Oncology working group and comprises apanel of international experts in spine stereotactic body radiotherapy (SBRT). Here, we present the group's first report on the challenges in standardising imaging-based assessment of local control and pain for spinal metastases. We review current imaging modalities used in SBRT treatment planning and tumour assessment and review the criteria for pain and local control in registered clinical trials specific to spine SBRT. We summarise the results of an international survey of thepanel to establish the range of current practices in assessing tumour response to spine SBRT. The ultimate goal of the SPINO group is to report consensus criteria for tumour imaging, clinical assessment, and symptom-based response criteria to help standardise future clinical trials.